Taste Masking of Prednisolone by Adsorption Method - Hiba Muhammed Suza Ali; Eman Bekir Al-Khedairy (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Prednisolone, a synthetic glucocorticoid with potent anti-inflammatory and immunosuppressive properties, is widely used to treat conditions such as asthma, allergies, and rheumatoid arthritis. Specific Background: Despite its therapeutic benefits, prednisolone’s intensely bitter taste negatively affects patient compliance, particularly in pediatric and geriatric populations. Knowledge Gap: Conventional taste-masking techniques often alter drug stability or release profiles, creating a need for simple, effective, and non-chemical masking approaches. Aims: This study aimed to mask the bitter taste of prednisolone using a physical adsorption method with Veegum® and Bentonite as adsorbents at varying concentrations. Results: Eight formulations were prepared and assessed for percentage yield, drug content, and in vitro taste masking. The optimal formula (F5, 1:5 drug-to-Veegum® ratio) achieved an 89% yield, 108.3% drug content, and reduced drug release in simulated saliva (pH 6.8) from 55% to 16.6% within one minute, without any detectable drug–excipient interaction by FTIR analysis. Novelty: This study demonstrates a successful use of physical adsorption as a straightforward and non-chemical method for prednisolone taste masking. Implications: The Veegum®-based adsorption approach offers a promising foundation for developing patient-friendly oral formulations of bitter drugs.Highlight : The study aimed to mask the bitter taste of prednisolone using the adsorption method. Veegum® at a 1:5 drug-to-adsorbent ratio showed the best taste masking result. FTIR analysis confirmed no chemical interaction between prednisolone and the adsorbents. Keywords : Prednisolone, Taste Masking, Adsorption Method, Veegum®, Bentonite